2018
DOI: 10.1371/journal.pone.0193054
|View full text |Cite|
|
Sign up to set email alerts
|

Parents’ knowledge, beliefs, and acceptance of the HPV vaccination in relation to their socio-demographics and religious beliefs: A cross-sectional study in Thailand

Abstract: Thailand has one of the world’s highest prevalence of cervical cancer, mainly caused by the human papillomavirus (HPV). HPV infections can successfully be prevented by vaccination, which is available at a cost but not yet implemented in the national vaccination program. Parents play a critical role in deciding whether to vaccinate their child against HPV. Thus, the aim was to examine the association between parents’ knowledge, beliefs, and acceptance of the HPV vaccination for their daughters, considering thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
46
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 56 publications
(87 reference statements)
11
46
1
4
Order By: Relevance
“…16 It has also been suggested that statements of evidence supporting effectiveness of cervical services could improve perceptions, especially as beliefs threaten existing programs; hence the need for context-specific evidence-based strategies advocated. [16][17][18] What this report contributes is an empirical data from Delta State, Nigeria. The implication is in the need to advance the knowledge of cervical screening procedure.…”
Section: Discussionmentioning
confidence: 99%
“…16 It has also been suggested that statements of evidence supporting effectiveness of cervical services could improve perceptions, especially as beliefs threaten existing programs; hence the need for context-specific evidence-based strategies advocated. [16][17][18] What this report contributes is an empirical data from Delta State, Nigeria. The implication is in the need to advance the knowledge of cervical screening procedure.…”
Section: Discussionmentioning
confidence: 99%
“…6 Also, a recent report has resonated that improvement in knowledge improves acceptance of cervical cancer prevention services. 11 What this paper contributes to the discourse is additional recommendation of need for the knowledge of female healthcare workers about Pap smear to be improved upon in order for them (i.e. health workers) to match the mass media in being source of information about cervical cancer screening.…”
Section: Discussionmentioning
confidence: 99%
“…Delta can be described as a micro Nigeria with numerous languages, cultural values, religions and beliefs; 9 which could impact on the uptake of cervical cancer screening and HPV vaccination. 4,10,11 Therefore, this study aims to investigate the demographics of women in conjunction with knowledge and perception of cervical cancer screening. Specifically, consideration will be on female civil servants in Delta State ministries; thereby cut across all educational classes, cultural groups and different reproductive age group.…”
Section: Statement Of the Research Problemmentioning
confidence: 99%
“…This observation is in agreement with the recent report from Thailand, which highlighted that parents' beliefs and knowledge level influence acceptance of HPV vaccination. 13 That is, improvement in level of knowledge of mothers about HPV can be attributed for the high willingness to vaccinate later and encourage others e.g. daughters to take up the vaccine.…”
Section: Yes Nomentioning
confidence: 99%
“…12 • Thailand-parents' beliefs and knowledge level were reported to influence acceptance of HPV vaccination. 13 Delta State is located at the coastal region bound on the south by Atlantic Ocean and composed of a microcosm of multiple social cultures. There are lots of oil exploration activities with associated immigrant employees allowing for high level of sexual activities, hence the importance of cervical screening and HPV vaccination cannot be overemphasized.…”
Section: Introductionmentioning
confidence: 99%